Relationship Between The Role Of Parents And Peers With Adolescent Smoking Behavior Of Boys At Sman 2 Meulaboh - Anita Tiara; Zakiyah (Science Midwifery, 2022)
Many teenagers smoke because teenagers like to try new challenges to find identity. The environment also influences the good and bad behavior of adolescents. Peers who are teenagers' environment often provide information or invite them to try smoking cigarettes. In addition, the family also has responsibility for the formation of norms in the process of forming children's behavior. The purpose of this study was to see the relationship between the role of parents and peers with the smoking behavior of adolescent boys at SMAN 2 Meulaboh. This study uses a type of quantitative research with a cross sectional design. The sample in this study was 133 people using a random sampling technique. Methods of data analysis using the Chi-Square test. The results showed the role of parents with a p value of 0, 021 and the role of peers with a p value of 0.003. The conclusion in this study is that there is a relationship between the role of parents and peers with adolescent smoking behavior at SMAN 2 Meulaboh. It is hoped that the role of parents, schools and health workers will be to provide more attention, information and support so that adolescents do not smoke or stop smoking.